Determinants and Effects of Reserve Prices in Hattrick Auctions - Florian Englmaier; Arno Schmöller (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
We use a unique hand collected data set of 6,258 auctions from the online football manager game Hattrick to study determinants and effects of reserve prices. We find that chosen reserve prices exhibit both very sophisticated and suboptimal behavior by the sellers. On the one hand, reserve prices are adjusted remarkably nuanced to the resulting sales price pattern. However, reserve prices are too clustered at zero and at multiples of e 50,000 as to be consistent with fully rational behavior. We recover the value distribution and simulate the loss in expected revenue from suboptimal reserve prices. Finally, we find evidence for the sunk cost fallacy as there is a substantial positive effect on the reserve price when the player has been acquired previously.
urn:nbn:de:bvb:19-epub-13228-6
Keywords: D12; D44; 330; Reserve Price; Auction Revenue; Inattention; Price Clusters; Sunk Cost Fallacy; Reservewährung; Preismanagement; Computerspiel; Internet; Welt